Analysis of nonlinear soil-structure interaction using partitioned method. Issue 162 (November 2022) - Lv, Hao; Chen, ShaoLin
Abstract: For the current state-of-practice in soil-structure interaction (SSI) of nuclear facilities, the strain-dependent characteristics of soil are considered indirectly via equivalent linear methods in the frequency domain, typically represented by the SASSI program. SSI analysis in the time-domain, although directly involving material nonlinearity of the soil, is inefficient in practice up to now. Based on Partitioned Analysis of SSI (PASSI), a method for nonlinear soil-structure interaction analysis is developed in this paper, by applying implicit time-step integration and explicit one with different time steps to nuclear island and to soil, respectively. The incremental equilibrium equation and explicit decoupling method are used to analyze the soil nonlinearity described by the Davidenkov model with simplified loading-reloading rules, which avoids solving algebraic equations and iteration processes. An asynchronous parallel algorithm for nonlinear SSI analysis is given. A simple example is given to verify the partitioned approach with explicit-implicit co-computation against the full-explicit approach. Seismic response characteristics of nuclear power plants are investigated by comparing responses of nonlinear analysis with linear analysis. Different results address the importance of nonlinear SSI analysis for the seismic performance of nuclear structures. Highlights: A NLSSI method based on Partitioned Analysis of soil-structure interaction (PASSI) is developed in this paper. Soil nonlinearity is described by Davidenkov model with simplified loading-reloading rules. The soil and structural subsystems can adopt different algorithms with different time steps independently. An incremental method is used to avoid algebraic equations iteration, which facilitates programming parallel code.